1984
DOI: 10.1080/14640748408402173
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Script and Phonology in Lexical Representation

Abstract: Two experiments were conducted to evaluate the role of script in lexical representation in bilinguals. The particular issue under investigation concerned the role of a script difference when the translations concerned are in all other respects identical. Does it provide a basis for the operation of unique functional entries in the lexicon, or is it, like case, treated as a pre-lexical attribute? The experiments contrasted the physically unrelated scripts used to depict Hindi and Urdu, North Indian languages wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 19 publications
2
31
0
2
Order By: Relevance
“…These results showed that reliable priming was consistently confirmed in both matched-script and cross-script conditions between the study and test phases, thereby replicating previous findings concerning script manipulations (Brown et al, 1984;Feldman & Moskovljevic, 1987;Naito & Komatsu, 1988). In thepresent experiment, however, differential effects of the script change on the size of priming were predicted between thetwo cross-script conditions, Katakana-study/Hiragana-test and Hiraganastudy/Katakana-test, following the explanation in terms of an imaging strategy during the encoding phase.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…These results showed that reliable priming was consistently confirmed in both matched-script and cross-script conditions between the study and test phases, thereby replicating previous findings concerning script manipulations (Brown et al, 1984;Feldman & Moskovljevic, 1987;Naito & Komatsu, 1988). In thepresent experiment, however, differential effects of the script change on the size of priming were predicted between thetwo cross-script conditions, Katakana-study/Hiragana-test and Hiraganastudy/Katakana-test, following the explanation in terms of an imaging strategy during the encoding phase.…”
Section: Methodssupporting
confidence: 78%
“…As introduced earlier, Naito and Komatsu (1988, Experiment 1) demonstrated the reliable size of cross-script priming between Kanji and Kana, although priming was greater in the matched-script condition. The similar pattern of cross-script priming has also been reported using the two types of visually distinct scripts, Hindi and Urdu (Brown, Sharma, & Kirsner, 1984) and Roman and Cyrillic (Feldman & Moskovljevic, 1987). Because both of the two distinct scripts were orthographically familiar in these previous studies, and, hence, one might have induced the visual image of the other, it is possible to explain the cross-script priming relying on the use of an imaging strategy.…”
Section: Methodsmentioning
confidence: 54%
“…Once again, little priming was obtained when items were spoken at study (6 msec averaging across studies), suggesting that cross-script priming was mediated by abstract orthographic codes. Lending further support to this conclusion, abstract word priming effects have been obtained between visually unrelated Hindi and Urdu scripts (Brown, Sharma, & Kirsner, 1984) and between Cyrillic and Roman scripts (Feldman & Moskovljevic, 1987). It should be noted, however, that the latter studies did not compare abstract visual priming with crossmodal priming, and thus it is possible that the effects were mediated by phonological or semantic representations.…”
Section: The Influence Of Various Contextual Variables On Primingmentioning
confidence: 70%
“…For example, robust priming is obtained between upper-and lowercase English words that share few perceptual features (Bowers, 1996) and between visually unrelated scripts of a language, such as the Kanji/Hiragana scripts of Japanese (Bowers & Michita, 1998), the Hindi/ Urdu scripts of Hindustani used in Northern India (Brown, Sharma, & Kirsner, 1984), and the Roman/Cyrillic scripts of Serbo-Croatian (Feldman & Moskovljevic, 1987). In addition, robust priming is obtained between morphologically related words (e.g., cars/car), and these effects cannot be attributed to the perceptual overlap between items, given that little or no priming is obtained between nonmorphologically related words that share the same degree of perceptual overlap, such as card/car (see, e.g., Bowers, Damian, & Havelka, 1999;Napps & Fowler, 1987).…”
mentioning
confidence: 99%